The effect of immediate verbal feedback on the efficiency and the effectiveness of swimming - Zaton, K.; Szczepan, S. (Baltic Journal of Health and Physical Activity, 2012)
Background: The aim of this study was to determine differences in stroke length and swimming time over a distance of 25m in a control and an experimental group from the provision of immediate verbal feedback.